Model Latihan Hayuswim Terhadap Kecepatan Renang 50 Meter Gaya Crawl Pada Atlet Kelompok Umur IV DI Klub Piranha Kota Tegal - Dwi Ayu Pangesti; Maftukin Hudah; Buyung Kusumawardhana (YLPK Mahardhika, 2022)
Swimming is a sport that has been known for a long time, which provides many benefits both physically and emotionally. This study aims to determine the effect of HayuSwim training on swimming speed of 50 meters crawl style in athletes age group IV at the Piranha club, Tegal City. This type of research is quantitative research with theresearch method Quasi Experiment Design. While the design of this study used a Pretest-Posttest Design. The samples used were 16 swimming athletes in Tegal City. The results of this study indicate that there is an increase in thetraining model HayuSwim to the swimming speed of 50 metersstyle crawl based on the results of the normality test calculated from the Asymp.Sig table. (2 tailed) shows that the results of the pretest and posttest data are more than the value of ? = 0.05, so it can be concluded that all data are normally distributed. Results from the homogeneity test table on Asymp.Sig. (2 tailed) shows 0.134 with a value of ? = sig 0.05, with this the sig value is greater than p> 0.05, it can be concluded that it is homogeneous. Hypothesis testing the average value in the pretest experimental group was 41.33 and the posttest was 40.86, an increase of 1.15%, while the average result of the control group was 40.47 pretest to posttest 40.44, an increase of 0.008% . The conclusion of this study is the effect oftraining HayuSwim on the swimming speed of 50 metersstyle crawl in athletes age group IV at the Piranha club Tegal City.